L’allegoria in Leopardi: l’eco dantesca - Giulia Abbadessa (Lexicon Philosophicum)
This article reflect on the presence of Dante’s allegory in Leopardi’s works. In fact, in the Zibaldone Leopardi considers allegory in a similar way to Dante in the Convivio in defending the autonomy of literature from excesses of allegorical interpretation. Furthermore in the Canti and Operette Morali Leopardi rewrites several allegories taken from Dante’s Commedia and Vita Nova as the personification of Love. The last aim of the article is to suggest that Leopardi, inspired by ancient tradition, is actually a “deformed Dante” as Baudelaire.